1999
DOI: 10.1046/j.1469-0705.1999.14060402.x
|View full text |Cite
|
Sign up to set email alerts
|

Early fetal megacystis between 11 and 15 weeks of gestation

Abstract: We found a high rate of associated malformations, especially intestinal malformations. The systematic evaluation of the intestinal enzymes in the amniotic fluid and urine samples might be an important aid in the diagnosis of multiple malformations, such as cloacal dysgenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 12 publications
9
60
0
12
Order By: Relevance
“…recent study of 16 cases with fetal megacystis between 11 and 15 weeks' gestation, 13 patients opted for termination of pregnancy 3 ; in four of these the fetal karyotype was abnormal. In Case 4 in our study, the patient decided on termination of pregnancy following reappearance of megacystis after a single aspiration.…”
Section: Vesicocentesis At 10-14 Weeks Carroll Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…recent study of 16 cases with fetal megacystis between 11 and 15 weeks' gestation, 13 patients opted for termination of pregnancy 3 ; in four of these the fetal karyotype was abnormal. In Case 4 in our study, the patient decided on termination of pregnancy following reappearance of megacystis after a single aspiration.…”
Section: Vesicocentesis At 10-14 Weeks Carroll Et Almentioning
confidence: 99%
“…Two studies reporting on 21 cases of fetal megacystis found that the incidence of chromosomal abnormality was 20-25% with the most common being trisomies 21, 18 and 13 2,3 . Other anomalies such as the VACTERL syndrome and cystic hygroma have also been associated with the condition 3,4 . Depending on the fluid volume, fetal karyotype may be determined either from the bladder aspirate or from simultaneous amniocentesis.…”
Section: Vesicocentesis At 10-14 Weeks Carroll Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs mainly because of abnormal distribution of collagenous and muscular fibers in this region. It is more common in males, being bilateral in 21 to 36% of the cases [17] . In our study we also found that the condition was more commonly associated with male babies.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital megacystis is an infrequently occurring anomaly investigated during prenatal ultrasound screening, with a prevalence of about 0.06 to 0.25% 1) . The outcome of this condition is different according to the gestational age at diagnosis 2) .…”
Section: Introductionmentioning
confidence: 99%